Bridging land value capture with land rent narratives - Vejchodská, Eliška (2022)
Urban land values have reached unprecedented levels in many parts of the world. Many scholars direct their research on their utilisation for public purposes. Two established research communities can be traced - the community referring to land value capture comprised mainly of urban planners and lawyers, and the community of economists discussing land rent. The relatively low level of interrelations between these communities prevents an effective sharing of their research outcomes. This contribution seeks to strengthen interconnections between these communities by characterising the narratives of both research communities, and synthesising their views. The research is largely built on systematic literature review with content analysis undertaken using the NVivo software. The analysis focussed on the terminology used, the specific causes of land value increase, rationales and instruments used for land value capture, and the purpose of using the collected money to investigate the interconnections between both research communities.